(untitled) (Indian Journal of Arid Horticulture, 2025)
Date palm (Phoenix dactylifera) is one of the oldest cultivated fruit crops in the world, and in India, it is believed to have been cultivated for more than four and a half centuries, where a significant area under cultivation is under the Kachchh district of Gujarat, which accounts for more than 85 % of the total area and production of the country (Muralidharan et al., 2022). Unlike other countries, harvesting of the date fruits is mostly done in the khalal stage while most countries harvest at their tamar stage due to the climatic conditions (incidence of early rainfall). Among the various cultivars evaluated, cultivar Barhee was recommended by Date Palm Research Station, Mundra, under AICRP-Arid Zone Fruits for cultivation in Gujarat in 2002 (Sharma et al., 2019), and since then Barhee has become the primary cultivar of the country, with a population of more than three lakh plants in Gujarat itself (data collected through personal communication).